2024
DOI: 10.1186/s12884-024-06536-6
|View full text |Cite
|
Sign up to set email alerts
|

Effective coverage of antenatal care services in Ethiopia: a population-based cross-sectional study

Zewditu Abdissa,
Kassahun Alemu,
Seblewengel Lemma
et al.

Abstract: Background Antenatal care (ANC) is a principal component of safe motherhood and reproductive health strategies across the continuum of care. Although the coverage of antenatal care visits has increased in Ethiopia, there needs to be more evidence of effective coverage of antenatal care. The 'effective coverage' concept can pinpoint where action is required to improve high-quality coverage in Ethiopia. Effective coverage indicates a health system's performance by incorporating need, utilization,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…We have shown that home-born neonates had lower coverage of essential newborn care with wealth-based inequities. A published paper from the same study population has shown that 70% of pregnant women had at least one antenatal care (ANC) visit decreasing to 40% with four or more [22]. Thus, it is crucial to improve the quality of ANC, including birth preparedness, counseling pregnant women to deliver in a facility, and making them aware of all essential newborn care practices that need to take place at the facility and at home.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that home-born neonates had lower coverage of essential newborn care with wealth-based inequities. A published paper from the same study population has shown that 70% of pregnant women had at least one antenatal care (ANC) visit decreasing to 40% with four or more [22]. Thus, it is crucial to improve the quality of ANC, including birth preparedness, counseling pregnant women to deliver in a facility, and making them aware of all essential newborn care practices that need to take place at the facility and at home.…”
Section: Discussionmentioning
confidence: 99%